Persahabatan: Sumbangsih Moralitas Tradisi Kristen bagi Moralitas Bangsa Indonesia - Hendrawan Wijoyo (Veritas : Jurnal Teologi dan Pelayanan, 2017)
Christians in Indonesia are often depicted as free riders who don’t contribute much to Indonesian’s independence and life as nation. This is a false claim. However, Christianity does need to offer a greater contribution, especially in the area of moral thought of Indonesia which is dominated by Islamic theology and secular ideas. Using the framework of Alasdair MacIntyre and Alister McGrath, this article constructs a theological and philosophical basis for Christianity’s contribution for the nation’s morality discussions. In the later part of this article, a Christian conception of friendship will be offered as an example of a Christian contribution.